2016
DOI: 10.1016/j.ijmyco.2015.09.001
|View full text |Cite|
|
Sign up to set email alerts
|

Correlating rrs and eis promoter mutations in clinical isolates of Mycobacterium tuberculosis with phenotypic susceptibility levels to the second-line injectables

Abstract: Objective To correlate rrs and eis promoter mutations, found in Mycobacterium tuberculosis (MTB) isolates,with corresponding Minimum Inhibitory Concentrations (MICs) of amikacin (AMK), kanamycin (KAN), and capreomycin (CAP). Methods Ninety MTB clinical isolates were analyzed in this study. MICs were determined by MGIT 960 for 59 isolates with resistance-associated mutations in the rrs and eis promoter gene regions and 31 isolates with wild-type sequences, as determined by the GenoTypeMTBDRsl (version 1) assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 17 publications
8
39
0
Order By: Relevance
“…The other four specimens were KAN s in both DST runs, indicating that these mutants had MICs below the tested KAN critical concentration. While eis promoter mutations have been well documented to confer only low-level KAN resistance (21,44), recent studies have found M. tuberculosis eis mutants to have broad KAN MIC ranges (0.625 to 32 g/ml) via liquid-based DST methods (45,46). As such, the eis promoter mutants identified in our study may have had MICs around the critical concentration.…”
Section: Rifmentioning
confidence: 60%
“…The other four specimens were KAN s in both DST runs, indicating that these mutants had MICs below the tested KAN critical concentration. While eis promoter mutations have been well documented to confer only low-level KAN resistance (21,44), recent studies have found M. tuberculosis eis mutants to have broad KAN MIC ranges (0.625 to 32 g/ml) via liquid-based DST methods (45,46). As such, the eis promoter mutants identified in our study may have had MICs around the critical concentration.…”
Section: Rifmentioning
confidence: 60%
“…Some of these drawbacks could be overcome by designing the assay to specifically address the detection of synonymous mutations as recently done for the Xpert Ultra; however, this strategy requires a priori knowledge of all the possible silent mutations in the targeted region. Fourth, clear understanding of the relationship between genotype and phenotype and clinical outcome is not always available, and several factors contribute in complicating the clinical interpretation of genetic polymorphisms …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, uncommon mutations at codon 1484 were also reported to confer resistance in KAN and AMK . Mutations at positons −10 and −35 of the promoter region of eis have been also been shown to confer resistance to KAN …”
Section: Mechanisms Of Drug Resistance In Mtbmentioning
confidence: 99%
“…As indicated by Georghiou et al (20), rrs MUT1 A1401G mutation is a moderate predictor of CAP resistance. Therefore, CAP resistance should be confirmed phenotypically prior to exclusion of the drug from a treatment regimen (21). There were 31 isolates identified as phenotypically XDR, and the GenoType MTBDRsl VER 2.0 assay achieved 97.0% agreement between the index and gold standard tests.…”
Section: Discussionmentioning
confidence: 99%